The Relationship Between Parenting Patterns and Providing Information On Adolescent Reproductive Health At SMA Negeri 3 Pematangsiantar - Iis May Dwi Mulyana (Institute Of Computer Science (IOCS), 2021)
Adolescence is often called the period of puberty where adolescents have a strong desire to know many new things, especially about reproductive health. The role of parents through the applied parenting is very necessary in providing information related to reproductive health. However, parents often consider it taboo if teenagers ask questions related to reproductive health so that teenagers will seek the information they need from irresponsible sources that allow them to adapt their deviant behavior. This study aims to identify the relationship between parenting and providing information about adolescent reproductive health at SMA Negeri 3 Pematangsiantar. This study used a cross sectional design. The sample of this research is 79 students. Sampling used proportional stratified random sampling and simple random sampling. The results of this study indicate that the parenting style that tends to be applied by adolescent parents is democratic (92.4%) with the provision of information about adolescent reproductive health in the good category (73.4%). The results of the analysis of the relationship between parenting and providing information about adolescent reproductive health measured by the Pearson product moment test indicate that parenting applied by parents has an important role in providing information to adolescents about adolescent reproductive health with a p value of 0.00 (? < 0.05) and correlation (r) = 0.420.